Investigation on the micromechanical damage mechanism of cement-stabilized macadam after multiple freeze-thaw cycles - Sun, Xingcheng; Wu, Xiaoyong; Zhao, Guofang; Yan, Zhanyou (Frontiers in Materials, 2025)
Cement-stabilized macadam is widely used in railway subgrade in cold regions. However, various diseases have occurred. In order to study the microscopic damage of cement-stabilized macadam after multiple cycles of freeze-thaw, the stress-strain curves were calculated by freeze-thaw tests in this paper. The discrete element model of cement-stabilized macadam constructed on the basis of discrete element theory was verified to be reasonable. After solving the linear/non-linear process of damage of cement-stabilized macadam, the relationship between the total damage variable and strain was obtained. The results show that as the number of freeze-thaw cycles increases, the initial damage variable increases. The results show that the more freeze-thaw cycles, the greater the initial damage variable. The damage variable formed after 20 freeze-thaw cycles is similar to that formed after 30 cycles. As the number of freeze-thaw cycles increases, the peak stress and particle contact area also decrease. The force chains are most numerous at the 215° position, and the number of force chains during the early stages of particle loading exceeds that in the later stages. The distribution of tangential and normal contact forces is symmetrical, with tangential stress distributed in an “∞” shape and normal contact force distributed in an “8” shape.